Scenario approach to shaping the group of the interior troops for performing the problems on reaction on exceeding situations - Adamchuk М. М.; Babkov, Yu. P.; Batsamut V. М. (Honor and Law, 2019)
On base of Scenario approach methods analysis, which is used in process of strategic management, way of the shaping of force and facilities of the interior troops for reaction on exceeding situations technical or natural types is offered